DIABETES MELLITUS SEBAGAI PREDIKTOR KEMAMPUAN HIDUP PASIEN IKTERUS OBSTRUKTIF KARENA TUMOR PANKREAS PASKA PINTASAN BILIODIGESTI - , REGINA ESTERLINA REHATTA, dr. Hendro Wiratmo, Sp.B., KBD. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The world prevalence of diabetes mellitus (DM) already reaches 171 million people. World Health Organization (WHO) predicts that Indonesia will be on the top 4 with about 12,4 million people diagnosed DM in year 2025. Eigthy five percent of patients with obstructive jaundice due to pancreatic tumor diagnosed at advance stage, require palliative treatment only. DM often found in cancer patients as comorbid. DM vascular complication will create ischaemic condition on the tumor site, which will inhibit tumor progressivity. Objective: To identify the difference of survival rate level on patients with obstructive jaundice due to pancreatic tumor performed biliodigestive shunting whom suffered DM compare to those without DM. Method: The study design was retrospective cohort. Survival analysis of both groups, DM and non-DM was performed by the Kaplan Meier curve. Cox regression bivariate analysis was used to determine the consistency of both groups survival rate difference. Results: There were 32 subjects included